Neutralization by Insulin of the Hypertensive Effect of Dermcidin Isoform 2: An Environmentally Induced Diabetogenic and Hypertensive Protein - Rajeshwary Ghosh; Sarbashri Bank; Rabindra Bhattacharya; Nighat N. Khan; A. Kumar Sinha (Cardiology Research and Practice)
The effect of dermcidin isoform 2 (dermcidin), an environmentally induced stress protein, was investigated on the genesis of diabetes mellitus and hypertension, the two major atherosclerotic risk factors. The role of dermcidin as an atherosclerotic risk factor related to the impaired systemic insulin level was investigated. Dermcidin was prepared by electrophoresis using plasma from the subjects with acute ischemic heart disease. Injection of 0.2 μM dermcidin in mice increased the blood glucose level from 98±2.45 mg/dL to 350 ±10.2 mg/dL which was normalized by the oral administration of acetyl salicylic acid (aspirin) after 24 h. Hypertensive subjects with systolic and diastolic blood pressure of 165 mm and 95 mm of Hg, respectively, had plasma dermcidin level of 95 nM. Ingestion of acetyl salicylic acid (aspirin) (150 mg/70 kg body weight) decreased the systolic and diastolic pressures to 125 mm and 80 mm of Hg, respectively, with decrease of dermcidin level to 15 nM. Incubation of kidney cortex cells with 0.2 μM dermcidin-inhibited synthesis of (r)-cortexin, an antihypertensive protein, and the basal (r)-cortexin level was reduced from 33 nM to 15 nM. Addition of 25 μunits of insulin/mL was found to reverse the inhibition of cortexin synthesis. The effect of dermcidin as a diabetogenic and a hypertensive agent could be controlled either by aspirin or by insulin.